Is Fiscal Policy Coordination in EMU Desirable? - Roel Beetsma; Xavier Debrun; Frank Klaassen (Center for Economic Studies and ifo Institute (CESifo), 2001)
It is widely argued that Europe's unified monetary policy calls for the international coordination at the fiscal level. We survey the issues involved with such coordination of fiscal policy as a demand management tool and we use a simple model to investigate the circumstances under which coordination may be desirable. It turns out that coordination is beneficial when the correlation of the shocks hitting the various economies is low. However, given the potentially adverse reaction by the ECB (as a result of free-riding and/or a conflict on the orientation of the policy mix), fiscal coordination is likely to be counterproductive when demand or supply shocks are highly symmetric across countries and the governments are unable to acquire a strategic leadership position vis-à-vis the ECB.
Keywords: 330; EMU; fiscal coordination; shocks; demand management